Rapid Assessment, Planning, Investigations and Discharge: Piloting the introduction of a senior doctor at triage model in an Australian paediatric emergency department. (21st August 2019) - Andrews, Sarah L; Lewena, Stuart; Cheek, John A
Abstract: Objective: We implemented a senior doctor at triage (SDT) pilot programme at The Royal Children's Hospital, Melbourne. We examined the impact on ED length of stay, seen on time and fail to wait (FTW) rates. Methods: A SDT model was piloted on Monday and Tuesday afternoons (pilot period) for 10 weeks, and compared with equivalent shifts for the preceding 10 weeks (pre‐pilot period). We determined the differences between the proportions of patients seen on time, length of stay in the ED of less than 4 h and FTW rate, as well as the medians of time to clinician and length of stay in ED. Results: A total of 2736 patients presented in the pilot period, and 2889 in the pre‐pilot. The percentage of patients who were seen on time improved from 52.3% to 68.7% (absolute difference 16.4%, 95% confidence interval [CI] 13.6–19.2%, P  < 0.001), the percentage of patients who had an ED length of stay of <4 h improved from 58.2% to 72.0% (absolute difference 13.8%, 95% CI 11.1–16.5%, P  < 0.001) and the FTW rate reduced from 12.5% to 7.1% (absolute difference 5.4%, 95% CI 3.8–7.0%, P  < 0.001) when the SDT model was operational. Conclusion: Implementation of a SDT model in a tertiary paediatric ED resulted in an increased proportion of patients being seen on time, having shorter length of stays in the ED and reduced the number of patients who FTW. Further studies are required to determine whether these improvements are sustained over time.